1988
DOI: 10.1104/pp.88.4.1026
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Steady State Pyruvate Dehydrogenase Complex Activity in Plant Mitochondria

Abstract: The requirements for reactivation (dephosphorylation) of the pea (Pisum sativum L.) leaf mitochondrial pyruvate dehydrogenase complex (PDC) were studied in terms of magnesium and ATP effects with intact and permeabilized mitochondria. The requirement for high concentrations of magnesium for reactivation previously reported with partially purified PDC is shown to affect inactivation rather than reactivation. The observed rate of inactivation catalyzed by pyruvate dehydrogenase (PDH) kinase is always greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Associated with the complex are the regulatory converter enzymes (pyruvate dehydrogenase kinase and phosphatase) which phosphorylate (inactivate) and dephosphorylate (activate) PDC (13,17). The pyruvate dehydrogenase protein phosphatase associated with the complex requires millimolar concentrations of Mg2" and the Mg2"-dependent activation is inhibited by Ca2" (2). Other (6) versus inactivation, in the present study].…”
Section: Discussionmentioning
confidence: 98%
“…Associated with the complex are the regulatory converter enzymes (pyruvate dehydrogenase kinase and phosphatase) which phosphorylate (inactivate) and dephosphorylate (activate) PDC (13,17). The pyruvate dehydrogenase protein phosphatase associated with the complex requires millimolar concentrations of Mg2" and the Mg2"-dependent activation is inhibited by Ca2" (2). Other (6) versus inactivation, in the present study].…”
Section: Discussionmentioning
confidence: 98%
“…Pyruvate, TPP and Na+ are inhibitory while K' and NH4+ are stimulatory. Other studies have shown that Mg2e is an inhibitor (2). The relative importance of these effectors and the interactions between them are still unclear.…”
Section: Mm)mentioning
confidence: 99%
“…Plant mitochondrial PDH kinase activity, assayed in intact or detergent-permeabilized mitochondria, purified from green leaf tissue of pea, is inhibited by pyruvate, dichloroacetate and Mg2e but is not affected by ADP, TPP or Ca2" (1)(2)(3) …”
Section: Biochemicalsmentioning
confidence: 99%
“…Initial studies of the regulatory properties of plant mPDC have been conducted in vitro using preparations that had been purified 20-to 300-fold (18)(19)(20)(21). Recently, we (2)(3)(4)16) have developed a method for assaying mPDC activity in situ using purified intact pea seedling mitochondria. Using this method, several observations on the regulation by reversible phosphorylation have been clarified and extended (2)(3)(4).…”
mentioning
confidence: 99%
“…Recently, we (2)(3)(4)16) have developed a method for assaying mPDC activity in situ using purified intact pea seedling mitochondria. Using this method, several observations on the regulation by reversible phosphorylation have been clarified and extended (2)(3)(4). This report continues our investigation of the role of product inhibition in regulation of PDC activity within intact mitochondria.…”
mentioning
confidence: 99%